2009
DOI: 10.2174/138945009789108774
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Therapy in Critically Septic Patients

Abstract: Critical illness and particularly sepsis are associated with a significant redox imbalance resulting from an increased production of oxidant species and a decrease in endogenous antioxidant defences. In critical patients sources of oxidative stress include the mitochondrial respiratory electron transport chain, xanthine oxidase activation, the respiratory burst associated with neutrophil activation, and arachidonic acid metabolism. Several endogenous antioxidants have been identified including enzymes, like su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 0 publications
2
49
0
1
Order By: Relevance
“…An animal model of sepsis utilizing sheep demonstrated that a large-bolus injection of Se (2 mg Se as sodium selenite) had more beneficial effects than continuous administration of Se (4.0 lg/kg per h) (263), although the conclusions of this study require follow-up investigation to determine if these results are duplicated in humans. In humans, treatment of critically septic patients with Se supplementation seems to improve clinical outcome in terms of infections and organ failure (8,205), but larger intervention studies are required before conclusive results can be obtained. Importantly, dosage and timing of Se administration (best results with > 500 lg/day) must be carefully evaluated so as to not endanger these patients (97).…”
Section: B Critical Illness Stress-induced Immune Suppressionmentioning
confidence: 99%
“…An animal model of sepsis utilizing sheep demonstrated that a large-bolus injection of Se (2 mg Se as sodium selenite) had more beneficial effects than continuous administration of Se (4.0 lg/kg per h) (263), although the conclusions of this study require follow-up investigation to determine if these results are duplicated in humans. In humans, treatment of critically septic patients with Se supplementation seems to improve clinical outcome in terms of infections and organ failure (8,205), but larger intervention studies are required before conclusive results can be obtained. Importantly, dosage and timing of Se administration (best results with > 500 lg/day) must be carefully evaluated so as to not endanger these patients (97).…”
Section: B Critical Illness Stress-induced Immune Suppressionmentioning
confidence: 99%
“…In critically ill patients, sources of oxidative stress include the mitochondrial respiratory electron transport chain [131], the respiratory burst associated with neutrophil activation [68], and arachidonic acid metabolism [132]. Melatonin exerts well-documented protective effects against septic shock in both animals and humans.…”
Section: Role Of Melatonin In Maintaining and Restoring Human Healthmentioning
confidence: 99%
“…Melatonin was shown to improve clinical outcome in terms of infection and organ failure in randomized clinical trials, thus being a promising antioxidant molecule in antioxidant therapy to combat sepsis [132][133][134]137].…”
Section: Role Of Melatonin In Maintaining and Restoring Human Healthmentioning
confidence: 99%
“…Besides, sepsis is associated with a significant redox imbalance. Recent studies pointed out that some anti-oxidant agents have beneficial effects in treating sepsis [5], such as N-acetylcysteine (NAC), MitoQ and deferoxamine (DFX) [6][7][8].…”
Section: Introductionmentioning
confidence: 99%